Tactics analysis of co-biding for Olympic Games for chengdu-chongqing economic circle under the new mechanism to Olympic hosting place election:based on the geodetector - Yang, L. F.; Rayner, M.; He, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
In todays normalized epidemic and global economic recession, hosting the Olympic Games is of great significance for urban development. At the same time, significant changes in the mechanism of hosting the Olympics have also brought new opportunities for the Chengdu-Chongqing Economic Circle to jointly host the Olympics. The article focuses on the phased characteristics of the real estate production mechanism during the Olympic Games and the 11 Olympic host sites from 1992 to 2032 as the research subjects to exploring the spatio-temoral evolution characteristics and influencing factors of the emergence of Olympic host sites through research methods such as geographic detector, and analyzing relevant strategies for the collaborative bidding of the Chengdu-Chongqing Economic Circle. The results indicate that the center of gravity of the Olympic host city is moving towards the southeast, showing characteristics of east-west expansion and north-south contraction. At the same time, its spatial accessibility is weakening, and the gap between the east and west is gradually narrowing. And the emergence of Olympic host sites is influenced by various factors, among which the annual growth rate of GDP, inflow of foreign direct investment, number of international inbound tourists, and per capita annual carbon dioxide emissions are important factors that affect the emergence of Olympic host sites. Based on the results, a constructive strategy is proposed to increase the attraction of foreign investment, fully showcase the charm of the city, and enhance the international tourism awareness, while ensuring environmental quality. The communication strategy emphasizes that the economy of the Chengdu-Chongqing Economic Circle is achieving high-quality development, and highlights that the Chengdu-Chongqing Economic Circle always adheres to the concept of green development, Provide theoretical and practical support for the collaborative bidding of the Chengdu-Chongqing Economic Circle for the Olympic Games.